Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.2337/diacare.22.9.1450
|View full text |Cite
|
Sign up to set email alerts
|

Plasma insulin, growth hormone, cortisol, and central obesity among young Chinese type 2 diabetic patients.

Abstract: In young Chinese type 2 diabetic patients, hyperinsulinemia, hypercortisolemia, and reduced plasma GH levels were closely associated with central obesity. Based on these findings, we postulate that maladaptive hormonal responses to rapid changes in lifestyle may have led to obesity and type 2 diabetes in these young patients. Alternatively, lifestyle-related obesity may have given rise to these hormonal changes. More studies are required to delineate the nature of these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 0 publications
5
70
1
Order By: Relevance
“…This result was in parallel with previous preliminary data which suggested that circulating cortisol concentrations were higher in patients with MS compared with healthy subjects, both in basal conditions and during dynamic stimulation [36,37]. In studies that included subjects with type 2diabetes alone, elevated basal plasma cortisol levels [38] have been also reported. In contrast, some studies have reported no association between cortisol and MS [39,40].…”
Section: Discussionsupporting
confidence: 81%
“…This result was in parallel with previous preliminary data which suggested that circulating cortisol concentrations were higher in patients with MS compared with healthy subjects, both in basal conditions and during dynamic stimulation [36,37]. In studies that included subjects with type 2diabetes alone, elevated basal plasma cortisol levels [38] have been also reported. In contrast, some studies have reported no association between cortisol and MS [39,40].…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the chronic consumption of high-GI foods, which would result in recurring, large postprandial fluctuations in blood glucose and insulin levels, could worsen insulin resistance in susceptible populations . The insulin resistance syndrome is already prevalent in young adults in diabetic-prone populations, including Chinese and other Asian populations (Lee et al, 1999). In Australia, Vietnamese women have one of the highest rates of gestational diabetes (Beischer et al, 1991;Shelly-Jones et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The activity of the HPA axis shows a clear circadian rhythm exhibiting a rapid rise during the latter half of the sleep cycle, with the highest levels occurring in the early morning (18) in parallel with the timecourse change of BP (19), suggesting the involvement of a diurnal change in HPA axis in the generation of MBPS. It was reported that T2DM patients exhibit higher baseline levels of serum cortisol (20). Although we did not monitor the diurnal change of serum cortisol in the current study, its serum level at 8:00 A.M. was significantly higher in those with insulin resistance than in those without.…”
Section: Discussionmentioning
confidence: 48%